2021
DOI: 10.1186/s12884-021-03579-x
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence and its relationship with quality of life in pregnant women during the outbreak of COVID-19 disease

Abstract: Background During the COVID-19 pandemic, pregnant women bear considerable physical and psychological stress because of their special conditions, which combined with other stress factors such as violence, makes their situation even more critical. This study aimed to investigate the prevalence of domestic violence and its relationship with quality of life in pregnant women during the COVID-19 pandemic. Methods This cross-sectional study was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
60
3
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 31 publications
(47 reference statements)
3
60
3
6
Order By: Relevance
“…Perhaps the most signi cant contribution that this study makes to the COVID-19 literature is the inclusion of economic abuse as part of measurement of intimate partner violence. Although researchers have highlighted the increase in intimate partner violence that has emerged as part of the COVID-19, both in the general population [49,51] and among pregnant women speci cally [52,53]. To the author's knowledge none of these studies included economic abuse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the most signi cant contribution that this study makes to the COVID-19 literature is the inclusion of economic abuse as part of measurement of intimate partner violence. Although researchers have highlighted the increase in intimate partner violence that has emerged as part of the COVID-19, both in the general population [49,51] and among pregnant women speci cally [52,53]. To the author's knowledge none of these studies included economic abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Although most studies examining the women's intimate partner violence experiences during the pandemic have focused on the general population, a small number studies have looked speci cally at the experiences of pregnant women. Naghizadeh and colleagues found one-third of their sample of 250 pregnant women seeking services at an obstetrics clinic in Iran reported experiencing intimate partner violence and those who had experienced abuse reported lower mental health quality of life [52]. Similarly, a study of 885 pregnant women in South Africa found approximately 12% of women t the criteria to be classi ed as having probable common mental health disorders; a higher percentage of these women reported anxiety about being infected with COVID, were severely food insecure during the lockdown and had experienced either psychological, physical, or sexual abuse by an intimate partner [53].…”
Section: Increased Stress During Covid-19 Pandemicmentioning
confidence: 99%
“…have reported a significantly high prevalence of domestic abuse in Tabriz during the COVID-19 pandemic and poor quality of life effectuated by it. [ 21 ] Hawcroft et al . conducted a systematic review and meta-analysis on the prevalence and outcomes of domestic abuse inferred that husbands are the most frequent abusers in the Arab region.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies focused on physical violence against health workers, specifically Iranian nurses [ 151 ], and mental illness in Chinese health workers who experienced aggression in their workplace [ 152 ]. Two studies specifically focused on pregnant women in Iran [ 153 ] and Ethiopia [ 154 ], documenting high rates of violence during the pandemic. Only one study included an evaluation of a violence prevention or mitigation program.…”
Section: Violence Incidence During the Covid-19 Pandemicmentioning
confidence: 99%